2001
DOI: 10.1007/bf01289422
|View full text |Cite
|
Sign up to set email alerts
|

Cellular redox state and activating protein-1 are involved in ascorbate effect on calcitriol-induced differentiation

Abstract: Ascorbate has been related to the differentiation of several mesenchymal cells including haematopoietic cells. We have previously demonstrated that ascorbate enhances the activity of 1 alpha,25-dihydroxyvitamin D3 (1 alpha,25(OH)2D3) on monocytic differentiation of HL-60 cells. Here, we show that ascorbate-mediated modification of cellular redox state and AP-1 (activating protein-1) DNA binding during early phases are related to the enhancing effect of ascorbate on differentiation. Ascorbate, but not its fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The mechanism involved in AA-2G-induced B cell differentiation remains to be determined. In this connection, it is noteworthy that AA has increased nuclear binding of the transcription factor AP-1 [36,37]. AP-1 has been shown to positively regulate expression of B-lymphocyte-induced maturation protein 1, one of key transcription factors in B cell terminal differentiation, and differentiation of activated B cells [38,39].…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism involved in AA-2G-induced B cell differentiation remains to be determined. In this connection, it is noteworthy that AA has increased nuclear binding of the transcription factor AP-1 [36,37]. AP-1 has been shown to positively regulate expression of B-lymphocyte-induced maturation protein 1, one of key transcription factors in B cell terminal differentiation, and differentiation of activated B cells [38,39].…”
Section: Discussionmentioning
confidence: 97%
“…In support of the role of plasma membrane redox system in cell signaling, it has been reported that extracellular signaling molecule growth factors, insulin and pituitary extracts activated NADH oxidoreductases of plasma membrane [56]. At least in the case of myeloid cell differentiation, it has been observed that modulation of the differentiation program by plasma membrane redox system activation includes modulation of intracellular second messengers and regulation of the activity of transcription factors [54,57]. Findings from studies on this topic suggest different mechanisms by means of which CoQ might exert these effects on cell signaling, which include the following.…”
Section: Physiological Roles Of Coqmentioning
confidence: 99%
“…Moreover, the activation of this system in myeloid cells enhances the differentiation to monocytes induced by 1α,25-dihydroxyvitamin D3 (Lopez-Lluch et al 1998;Quesada et al 1996). In this effect, we found that PMRS activation modulates second messengers such as cAMP that regulate the activity of transcription factors implied in differentiation (Lopez-Lluch et al 2001;Lopez-Lluch et al 1998;Quesada et al 1996).…”
Section: Regulatory Role Of Coq In Plasma Membranementioning
confidence: 69%
“…We demonstrated that both, CytB5Rase and NQO1 are induced under caloric restriction in liver of both rats(De Cabo et al 2004) and mice(Lopez-Lluch et al 2005b). Activation of PMRS is also associated with the enhancement of monocyte differentiation through induction of cAMP(Lopez-Lluch et al 2005a), an effect that was also associated with changes in mitochondrial physiology(Lopez-Lluch et al 2001). Furthermore, activity of PMRS has been associate with the maintenance of mitochondrial function and the delay in senescence progression in a senescence-accelerated mice model(Tian et al 2014) in a process associated with the increasing of cAMP and the activation of Sirt1 and PGC1-α.…”
mentioning
confidence: 80%